(untitled) (Health Renaissance, 2015)
Background: Systemic hypotension is seen frequently after spinal anesthesia in obstetric population and if untreated can lead to maternal and fetal complications. Ephedrine, via various routes, has been used both as prophylaxis and treatment of this hypotension. Oral ephedrine has been found to be effective in prevention of hypotension in non obstetric patients after neural block. Objective: To study the efficacy of oral ephedrine in prevention of hypotension following spinal anesthesia in LSCS and to assess the neonatal outcome. Methods: It was a randomized, controlled double blinded study involving 100 parturients undergoing LSCS. Total duration of study was two years. A preformed structured proforma was used to record the data incidence of hypotension and neonatatal APGAR score were the main outcome variables. This study was carried out in 100 ASA physical status I and II patients admitted for emergency and elective LSCS. Fifty patients received placebo and 50 patients received prophylactic ephedrine orally, before spinal anesthesia. The two groups were compared in respect of their incidences of hypotension and maintenance of SBP and neonatal outcome. Results: The incidence of hypotension was much higher in patients who received placebo than who received prophylactic ephedrine orally (19 vs. 6). APGAR score for assessment of neonatal wellbeing was similar in two groups. Conclusions: The prophylactic oral ephedrine 30 mg, given 30-45 minutes before LSCS, is a simple and effective measure to prevent hypotension following spinal anesthesia and it does not have any adverse effect on neonatal outcome. Health Renaissance 2014;12(2): pp: 118-123